The tradition about the mons caelius - Malloch, Simon (Franz Steiner Verlag, 2018)
This essay offers three arguments concerning the ancient tradition about the mons Caelius. (1) Tacitus’ digression on the name of the mons Caelius at Annals 4.65 provides a useful framework for interpreting the complexity of the tradition: Caeles Vibenna should be regarded as a constant feature, his chronological context as an unstable feature that was recognised as such. (2) Claudius’ report of Etruscan auctores on the naming of the mons Caelius in his speech of A.D. 48 about the Gauls, correctly emended, offers a unique etymology that cannot be reconciled with Roman accounts. (3) The presence of appellitare in Tacitus’ digression and Claudius’ speech is normally assumed to prove Tacitus’ debt to Claudius, but this assumption cannot be sustained in the face of their fundamentally irreconcilable treatments of Caeles Vibenna. Tacitus used appellitare independently of Claudius, who was not a source of Ann. 4.65.